MiR-196a Promotes Pancreatic Cancer Progression by Targeting Nuclear Factor Kappa-B-Inhibitor Alpha - Huang, Fengting; Tang, Jian; Zhuang, Xiaohong; Zhuang, Yanyan; Cheng, Wenjie; Chen, Wenbo; Yao, Herui; Zhang, Shineng (PloS one, 2014)
Aberrant expression of miR-196a has been frequently reported in different cancers including pancreatic cancer. However, its function in pancreatic cancer has not been fully elucidated. Here, we investigated the expression pattern and the biological role of miR-196a in pancreatic cancer cell lines, as well as its interaction with a metastasis-related gene, nuclear factor-kappa-B-inhibitor alpha (NFKBIA). We demonstrated that miR-196a was up-regulated in human pancreatic cancer cell lines compared with immortalized pancreatic ductal epithelial cells by means of microRNAs microarray and qRT-PCR. Furthermore, down-regulation of miR-196a in PANC-1 suppressed its proliferation and migration with an increase in G0/G1 transition and decreased expression of Cyclin D1 and CDK4/6. Meanwhile, an increased expression in E-cadherin and decreased expression in N-cadherin and Vimentin were also observed. We identified a novel miR-196a target, NFKBIA, and down-regulation of miR-196a enhanced the expression of NFKBIA protein. Luciferase assay confirmed that NFKBIA was a direct and specific target of miR-196a. Silencing NFKBIA in PANC-1 cells enhanced its proliferation and migration. Taken together, our findings indicate that miR-196a is highly expressed in pancreatic cancer cell lines, and may play a crucial role in pancreatic cancer proliferation and migration, possibly through its downstream target, NFKBIA. Thus, miR-196a may serve as a potential therapeutic target for pancreatic cancer.